2009
DOI: 10.2135/cropsci2008.05.0290
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and the Effectiveness of Early‐Generation Selection for Soft Winter Wheat Quality and Gluten Strength

Abstract: Selection for milling and baking quality in wheat (Triticum aestivum L.) head‐rows could increase the efficiency of most soft winter wheat (SWW) breeding programs. We evaluated whole grain‐wheat meal (WM) assays for their ability to select lines with acceptable SWW quality and high gluten strength in early‐generations and estimated heritability of SWW quality and gluten strength. One hundred fourteen lines from a cross of strong and weak gluten parents was assessed over three location‐years. Flour quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
2
16
1
Order By: Relevance
“…This may be explained by the sedimentation value use in the early breading process to select genotypes for high baking quality as reported, e.g. by Knott et al (2009), Hartl et al (2011) and Souza et al (2012). …”
Section: Discussionmentioning
confidence: 84%
“…This may be explained by the sedimentation value use in the early breading process to select genotypes for high baking quality as reported, e.g. by Knott et al (2009), Hartl et al (2011) and Souza et al (2012). …”
Section: Discussionmentioning
confidence: 84%
“…Within United States soft wheat germplasm, fl our-milling yield is highly heritable and an important measure of soft wheat quality (Baenziger et al, 1985;Guttieri et al, 2001Guttieri et al, , 2004Souza et al, 2008;Knott et al, 2009). Within United States soft wheat germplasm, fl our-milling yield is highly heritable and an important measure of soft wheat quality (Baenziger et al, 1985;Guttieri et al, 2001Guttieri et al, , 2004Souza et al, 2008;Knott et al, 2009).…”
Section: Researchmentioning
confidence: 99%
“…The greatest concentrations of minerals are in the aleurone and then the bran layers, the same layers that contribute to increased water absorption within a soft wheat. Previous work with whole grain ground-wheat samples indicated that cultivars varied signifi cantly for water absorption in ground meal and that the heritability components of fl our water absorption, such as damaged starch content, exceeded 60% (Guttieri et al, 2004, Knott et al, 2009. Greater fl our water absorption decreases the suitability of a fl our for high-sugar products like cookies and cakes (Guttieri et al, 2001).…”
Section: Selecting Soft Wheat Genotypes For Whole Grain Cookiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, different aspects of flour quality are profiled by the flour SRC values (Gaines 2000). Smaller-scale SRC methods have been developed to assess whole wheat meal and as an early generation selection tool in breeding programs (Bettge et al 2002;Guttieri et al 2004;Knott et al 2009). Although almost all of these studies have reported on the relationships between SRC values and the quality of the sugar-snap cookie, little information has been available with respect to the relationships between SRC tests and the baking quality of Japanese sponge cake.…”
mentioning
confidence: 99%